(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Congenital anomalies of the kidney and urinary tract (CAKUT) account for 30-50% of pediatric end-stage renal disease and remain underdiagnosed in primary care settings. This prospective-retrospective study enrolled 247 children aged 0-14 years over five years. Prenatal detection was achieved in 63.2% of cases. Early intervention reduced surgical complication rates by 38.8% and significantly preserved long-term differential renal function.